Social welfare issues of older population in Malaysia - Ismail, Zainab; Wan Ahmad, Wan Ibrahim (International digital organization for scientific information (IDOSI), 2014)
In recent years older population is growing globally.The growth of this population is said to be the 21st century phenomenon.Never before in the history of demography has the world contained a high number and proportion of populations living to the age of 65 and over.This article, originated from a qualitative study, discusses the growth of older persons in Malaysia and attempt to explore social welfare issues arise.To explore these issues, this qualitative study was conducted an in-depth interview with three key informants.The interview was recorded.Upon completing the interview, five issues of the welfare of older persons are traced which are the changes of family, youth migration to city, support and care system, health problems and employment and financial security. These issues will be facing by all if one reaching older ages.